Media Performance and Conflict Management: A Case Study of Indo- Pak Relations after the Mumbai Attacks - Azmat Rasul (JSSH, 2023)
South Asia is a conflict zone where media have been very influential in generating mutually hostile perceptions. Many analysts of Indo-Pakistan relations believe that jingoistic attitude of media in the sub-continent obstructs all peace moves in the region. Media have been responsible to increase the level of tension between both countries and resultantly incapacitate the governments’ abilities to take concrete steps towards peace.